Spiritual intelligence and mindfulness as sources of transformational leadership - D’Brot Calderón, Jorge Edmundo (Pontificia Universidad Católica del Perú, 2017)
The transfer rate of transformational leadership training is considered marginal; it is estimated that less than 30% of leaders who participate in the training change their behavior once back in the workplace. Most quantitative investigations have focused on predictors of transformational leadership, providing insufficient information about possible internal driving forces that influence leaders to behave in a transformational manner; furthermore, some correlations of those predictors with specific dimensions of transformational leadership have not been thoroughly explained. In the present quantitative, survey-based, cross-sectional research, we tested the effects of spiritual intelligence and mindfulness on transformational leadership behavior patterns among a sample of 542 leaders in Peru, with the results suggesting that mindfulness partially mediates the effects of spiritual intelligence on transformational leadership. Based on these findings, we propose that introducing spiritual intelligence and mindfulness training as part of the traditional curricula for transformational leadership training will improve the transfer of knowledge to leaders
Keywords: Liderazgo; Inteligencia emocional; Administración -- Aspectos psicológicos; Atención; Investigación cuantitativa; https://purl.org/pe-repo/ocde/ford#5.02.04